Respuesta :
To solve:
first, bring everything to one side so we have a quadratic equation.
y^2-5y-36=0
then factor.
(y-9)(y+4)=0
put each value to zero.
y-9=0
y=9
y+4=0
y=-4
Answers: y=9, and y=-4
first, bring everything to one side so we have a quadratic equation.
y^2-5y-36=0
then factor.
(y-9)(y+4)=0
put each value to zero.
y-9=0
y=9
y+4=0
y=-4
Answers: y=9, and y=-4
this is a quadratic equation
y^2 - 5y - 36 = 0
Factoring
(y - 9)(y + 4) = 0
y-9 = 0 giving y = 9 or y+4 = 0 giving y = -4
Solution set is {-4, 9}
y^2 - 5y - 36 = 0
Factoring
(y - 9)(y + 4) = 0
y-9 = 0 giving y = 9 or y+4 = 0 giving y = -4
Solution set is {-4, 9}